CURRENT APPROACHES TO THE PREVENTION, EVALUATION AND TREATMENT OF COMPLICATIONS DURING ENDOVASCULAR CORONARY ARTERY INTERVENTIONS. PART II. DISSECTION OF THE LEFT MAIN CORONARY ARTERY AND THE RIGHT CORONARY ARTERY, INVOLVING THE AORTA - S. A. Prozorov (Неотложная медицинская помощь)
AIM OF THE STUDY. The aim of the study is to analyze frequency and causes of dissection of the left main coronary artery and the right coronary artery dissection involving the aorta related to diagnostic and endovascular interventions as well as to describe modern approaches to treatment for these complications.MATERIAL AND METHODS. The results of endovascular interventions in 2,317 patients were studied. Dissection of the left main coronary artery developed in 3 patients (0.13%), spreading to the aorta in 1 case.RESULTS. coronary stent implantation closing the dissection of the left main coronary artery has been effective in 2 patients, and in 1 patient the dissection has not been immediately revealed.CONCLUSIONS. A stent implanted to close the beginning of the dissection (“the entrance gate”) is the primary method for elimination of complications. conservative management of patients is possible if relatively limited dissection has no tendency to spread.